Unified design approach for structural concrete based on eurocode 2 - Fong, A.W.Y (University Malaysia Sarawak, (UNIMAS), 2005)
In this project, a unified design approach was proposed for partially prestressed concrete (PPC) which incorporate fully reinforced concrete and fully prestressed concrete as according to Eurocode 2. The purpose of this project is to provide a platform for solving the problems that might occur in designing partially prestresseed concrete using the new design code of Eurocode 2